Factors associated with pathological complete remission after neoadjuvant chemoradiotherapy in locally advanced rectal cancer: a real-world clinical setting - Lin, Minglin; Liu, Junsheng; Lan, Chongyuan; Qiu, Ming; Huang, Wei; Liao, Cun; Zhang, Sen (Frontiers in Oncology, 2024)
Objective: This study aims to identify factors associated with achieving a pathological complete remission (pCR) in patients with locally advanced rectal cancer (LARC) after neoadjuvant chemoradiotherapy (nCRT). Methods: We conducted a cohort analysis of 171 LARC patients who underwent curative resection post-nCRT at the First Affiliated Hospital of Guangxi Medical University between January 2015 and December 2021. The data encompassed clinical and pathological information. Univariate and binary logistic regression multivariate analyses were employed to examine the factors influencing pCR achievement after nCRT. Kappa value tests were utilized to compare clinical staging after nCRT with postoperative pathological staging. Results: Postoperative histopathology revealed that of the 171 patients, 40 (23.4%) achieved TRG 0 grade (pCR group), while 131 (76.6%) did not achieve pCR, comprising 36 TRG1, 42 TRG2, and 53 TRG3 cases. Univariate analysis indicated that younger age (p=0.008), reduced tumor occupation of intestinal circumference (p =0.008), specific pathological types (p=0.011), and lower pre-nCRT CEA levels (p=0.003) correlated with pCR attainment. Multivariate analysis identified these factors as independent predictors of pCR: younger age (OR=0.946, p=0.004), smaller tumor occupation of intestinal circumference (OR=2.809, p=0.046), non-mucinous adenocarcinoma pathological type (OR=10.405, p=0.029), and lower pre-nCRT serum CEA levels (OR=2.463, p=0.031). Clinical re-staging post-nCRT compared to postoperative pathological staging showed inconsistent MRI T staging (Kappa=0.012, p=0.718, consistency rate: 35.1%) and marginally consistent MRI N staging (Kappa=0.205, p=0.001, consistency rate: 59.6%). Conclusion: LARC patients with younger age, presenting with smaller tumor circumferences in the intestinal lumen, lower pre-nCRT serum CEA levels, and non-mucinous adenocarcinoma are more likely to achieve pCR after nCRT. The study highlights the need for improved accuracy in clinical re-staging assessments after nCRT in LARC.